PENGARUH KEBIJAKAN MODAL MINIMAL TERHADAP MINAT MAHASISWA BERINVESTASI SAHAM (STUDI PADA GALERI INVESTASI POLITEKNIK NEGERI MANADO) - Martine Lapod; Effendy Rasjid (Manis: Jurnal Manajemen dan Bisnis, 2022)
The Investment Gallery at the Manado State Polytechnic Campus is one of the forums or educational facilities that was formed with the aim that students can learn, get to know various kinds of investment products in the capital market which ultimately targets students to want to become investors from an early age. Minimum Investment Capital which is the policy of the Indonesia Stock Exchange to attract public interest in investing, namely with a minimum investment capital of IDR 100,000, - this is considered affordable by the public and also by students as millennial investors. This can be a problem that affects student interest in investing. The results of data processing using the SPSS 26 program obtained a tcount value of 1.237 with a significance of 0.000. Because the tcount value of 1.237 is greater than the ttable value of 1.659 with a significance value of 0.000 <0.05, it can be concluded that the tested group has a significant (significant) difference. These results mean that partially Minimum Investment Capital has a significant effect on Student Interest in Investing in Stocks at Manado State Polytechnic. The results of the correlation analysis obtained r = 0.120 categorized as having a strong and positive relationship between the variable Minimum Investment Capital and Student Interest in Investing Stocks in the Capital Market Suggestions must be socialized regarding the minimum amount of capital needed in investing in stocks which can later affect student interest in investing in stocks.